Estudo microestrutural e reológico da liga reciclada de alumínio A380 modificada pela adição de estrôncio - Ferreira, João Paulo Gabre (2017)
The A380 aluminum alloy is one of the main raw materials used in the die casting industry, and has already been the subject of research in the field of semi-solid materials. However, there is a lack of studies about this material when modified by Sr and used as semi-solid material. Thus, this work aims to analyze the microstructure and rheological behavior of this alloy in 4 different conditions. The first condition is as cast, the second one is with grain refinement of the Al-α phase, and the other two conditions, and besides the grain refining, was also added 200ppm and 600ppm of Sr. Initially, metallographic analyzes were performed to evaluate the efficiency of the grain refinement and the eutectic modification in the A380 alloy. The main results indicated that the Al-5Ti-1B refining alloy was able to significantly reduce the grain size of the primary phase, as well as the addition Of Sr was able to modify the morphology of the Al-Si eutectic phase. Then, analyzes via Scheil equation and DSC were performed to evaluate the evolution of the solid fraction along the temperature for the four conditions established for the A380 alloy, as well as to set the temperature equivalent to 60% of Fs (Solid Fraction). The results pointed to a slight divergence between the data obtained by the two techniques, where the DSC temperatures were slightly higher than those obtained via the Scheil equation. However, no significant variation was found among 4 conditions analyzed. Therefore, in this work, the chosen temperature of 60% of Fs was 562°C, obtained via the Scheil equation. About the semi-solid behavior, the morphological evolution of the materials was analyzed after the globularization thermal treatment with holding times of 0, 30 and 90 seconds and a solid fraction of 60%. The analysis by conventional and polarized light metallography, point to a more efficient globularization in the refined as well as in the modified materials, the best results was found for the refined and 200ppm Sr modified condition. Finally, the hot compression test was performed in the alloys, using the holding times and Fs previously established. The results indicate that both the grain refinement and the Sr modification have influence on the rheological behavior of the A380 alloy.